Soliton Self-Frequency Shift of µJ-Level Pulses at MHz Repetition Rates for Tunable and Broadband THz Generation Using an Organic Crystal - Lippl, Markus; Couture, Nicolas; Butryn, Martin; Menard, Jean Michel; Joly, Nicolas Y.; Tani, Francesco (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We present a tunable light source based on soliton self-frequency shift in hydrogen filled hollow-core fibers with record breaking pulse energy and use it to pump a DSTMS crystal for efficient and broadband terahertz generation.
CRIS-Team Scopus Importer:2024-10-04